Proceedings of the 2nd International Conference on Civil, Materials and Environmental Sciences 2015
DOI: 10.2991/cmes-15.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sewage Sludge as Raw Material in the Manufacture of Roofs

Abstract: Abstract-The present study verifies the possibility of incorporating sewage sludge in the production of ceramic mass for ceramic roof tiles. Domestic sewage sludge and clay from ceramic industries of the northeast region of Brazil were used. The raw materials were chemically and mineralogically characterized. Seven hundred and fifty tiles were manufactured using different concentrations of sludge (2%, 4%, 6%, 8% and 10% of sludge dry mass). The high amount of organic material (71%) from the sludge shows itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Overall, paper sludge from industrial waste has a high potential to replace the existing reinforcement filler in thermoplastic polymers (Elloumi et al 2016). Ingunza et al (2015) incorporated sewage sludge (at concentrations of 2%, 4%, 6%, 8%, and 10% dry mass) with clay to produce ceramic roof tiles. Water absorption increased with the addition of sludge into the clay.…”
Section: Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, paper sludge from industrial waste has a high potential to replace the existing reinforcement filler in thermoplastic polymers (Elloumi et al 2016). Ingunza et al (2015) incorporated sewage sludge (at concentrations of 2%, 4%, 6%, 8%, and 10% dry mass) with clay to produce ceramic roof tiles. Water absorption increased with the addition of sludge into the clay.…”
Section: Sludgementioning
confidence: 99%
“…This is the main drawback of using sludge for construction materials. The amount of sludge recommended by Ingunza et al (2015) in ceramic mass used to manufacture roof tiles was 4% of dry weight sludge. However, Kutuk and Oguz (2016) found that the tensile strength of their studied composite increased when the content of sewage sludge ash particles was increased to 20%, which was then followed by a decrease in tensile strength when the sewage sludge ash particle content was increased beyond 20%.…”
Section: Sludgementioning
confidence: 99%
“…Five mixtures were prepared using different proportions of sludge ranging from 2% to 10% by weight as a partial replacement for clay. Because of the high organic matter content in the sludge (>70%), the addition was limited to 4% by weight so as not to negatively affect water absorption and flexural strength [9]. On the other hand, De Silva et al studied the possibility of replacing clay with rice husk ash (RHA) in the preparation of ceramic roof tiles.…”
Section: Introductionmentioning
confidence: 99%
“…In floor tile production, clay was replaced with sewerage sludge by 7 % [7]. For roof tile production, clay was replaced with waste RHA by 10 % [8], ceramic sludge by 20 % [9], sewage sludge by 4 % [10], rock dust by 40 % [11], glass waste by 10 % [12], and granite waste by 40 % [13]. However, in previous studies [3][4][5][6][7][8][9][10][11][12][13], investigations were focused on clay replacement with single waste material.…”
Section: Introductionmentioning
confidence: 99%